2007
DOI: 10.1177/0269215507074056
|View full text |Cite
|
Sign up to set email alerts
|

One question as a screening instrument for depression in people with multiple sclerosis

Abstract: One-question interview is a useful tool for screening for depression in people with multiple sclerosis as it confirms existing depression (sensitivity 91%), but the results should be treated with caution if the person denies mood problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…Some authors argue for directly asking patients whether they think they are depressed rather than opting for a wording of feeling depressed. However, results are inconsistent [49,50]. Similar findings have been reported in cognitive interviews during the German translation of the IPOS [25] and its Italian translation [51].…”
Section: Discussionmentioning
confidence: 56%
“…Some authors argue for directly asking patients whether they think they are depressed rather than opting for a wording of feeling depressed. However, results are inconsistent [49,50]. Similar findings have been reported in cognitive interviews during the German translation of the IPOS [25] and its Italian translation [51].…”
Section: Discussionmentioning
confidence: 56%
“…We can confirm that the use of this screening tool is feasible in everyday clinical practice as was shown by us in a previous study for people with multiple sclerosis. 7 It may be concluded that if the person with hereditary spastic paraplegia confirms mood problems then the possibility of depression is high. If the person answers anything other than 'Yes' to the one-item interview then he or she should be treated with more careful attention and referred for further testing in spite of the negative answer before the final treatment plan is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…detected 85-90% of patients with depression in primary care 4,5 and has been found to be a sensitive tool for detecting depression in everyday clinical practice among people with multiple sclerosis. 6,7 The hereditary spastic paraplegias are neurodegenerative disorders of the motor system characterized by slowly progressive lower limb spasticity. The clinical course of hereditary spastic paraplegia may be presented in two forms.…”
Section: Introductionmentioning
confidence: 99%
“…Hart, Werneke, George, and Deutscher (2012) report data from over 10,000 physical therapy outpatients which suggests that even a single mental health screening question may be valid and reliable. However, Reme, Lie, and Eriksen (2014), in research with clients who had chronic lower back pain, and Vahter, Kreegipuu, Talvik, and Gross-Paju (2007) with people with multiple sclerosis, are among many researchers who have found that while single question screening for depression may have adequate sensitivity (correctly identifying a person with depression, 'true positive') it is often lacking in specificity (correctly identifying a person who does not have depression, 'true negative'). That is, this truncated approach to screening tends to be over inclusive.…”
Section: Mental Health Screeningmentioning
confidence: 99%